Comparison between nitrogen- oil- mist and air-oil- mist condition when turning of hardened tool stainless steel - Handawi, M.; Elshwain, A.; Mohd Yusof, N.; Redzuan, N.; Kurniawan, Denni (2014)
© (2014) Trans Tech Publications, Switzerland. Minimum quantity lubrication (MQL) is a technique which sprays a small amount of lubricant to the cutting zone with the aid of compressed air. MQL has become an attractive option to dry and flood cutting in terms of being able to increase tool life and reduce the cost of the product. However, machining under MQLseems to be limited by cutting temperature, this is because at high speeds, the oil mist becomes evaporated. Therefore, in this study the use ofnitrogen gas and air as cooling mediumin combination with oil mist as a lubricant was compared in order to improve the machining performance when turning hardened stainless tool steel (STAVAX ESR) with hardness 48 HRCusingwiper coated carbidecutting inserts. The results show that the use of nitrogen with oil mist prolongs the tool life compared to the use of air and oil mist. Also better product surface Finnish was obtained when using nitrogen gas with oil mist.